Organizational Communication Patterns of PSI Jakarta in the Implementation of the Internship Program Batch 17 - Citra Ayu Shafinas; Rici Tri Harpin Pranata; Fahmi Fuad Cholagi (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
This study aims to analyze the communication patterns employed in the implementation of the PSI Jakarta Internship Program Batch 17, with a focus on communication effectiveness in supporting the program’s objectives. The research adopts a descriptive qualitative approach within a constructivist paradigm, which views reality as a continuously evolving human construct. Data were collected through observation, in-depth interviews, and document analysis. The research subjects comprised PSI Jakarta administrators and members directly involved in the internship program. The findings reveal three communication patterns utilized in the program’s execution: formal communication, informal communication, and socialization mechanisms. Formal communication was conducted through annual and weekly work meetings, while informal communication occurred more frequently via WhatsApp and in-person office meetings. For program socialization, information was disseminated through social media platforms such as Instagram, LinkedIn, and WhatsApp Blast. The study also found that communication barriers primarily occurred among persons in charge (PICs) in terms of cross-departmental coordination. Nevertheless, communication between upper management and PICs proceeded smoothly. These findings highlight the importance of effective communication patterns in ensuring the success of political internship programs that involve multiple stakeholders with diverse roles.